Framing Konflik Iran–Israel dalam Media Internasional: Analisis Komparatif CNN dan Al Jazeera - Putra, Romi Iriandi; Maulana, Mahesa; Andreas, Rino (Jurnal Audiens, 2026)
This study critically examines the competing media frames of the Iran-Israel conflict involving the United States in CNN and Al Jazeera using Robert N. Entman's framing model. It aims to uncover how ideological and geopolitical factors shape the construction of conflict narratives in international media. Using a qualitative framing analysis, this study analyzes 10 news articles published between 1-7 March 2026. The analysis focuses on four elements: define problems, diagnose causes, make moral judgments, and treatment recommendations. The findings reveal a systematic divergence in framing. CNN constructs the conflict within a security-oriented perspective, positioning Iran as a threat while normalizing the actions of the United States and its allies. In contrast, Al Jazeera advances a counter-hegemonic narrative by emphasizing humanitarian impacts and portraying Iran's actions as resistance to external intervention. These differences demonstrate that global media act as ideological agents that produce competing geopolitical meanings. This study contributes to framing theory by highlighting media discourse as a site of contestation that shapes divergent global perceptions of international conflict.